Erratum: A new species of scaly blenny of the genus Labrisomus (Actinopterygii: Labrisomidae) from the tropical West Atlantic. Zootaxa, 2015, 62–68. - Sazima, I.; Carvalho-Filho, A.; Gasparini, J. L.; Sazima, C. (Zootaxa, 2010)
Erratum